2018
DOI: 10.3892/mmr.2018.8972
|View full text |Cite
|
Sign up to set email alerts
|

Dextran‑coated superparamagnetic iron oxide nanoparticles activate the MAPK pathway in human primary monocyte cells

Abstract: With the increase in applications of superparamagnetic iron oxide nanoparticles (SPIONs) in biomedicine, it is essential to investigate the bio‑security of these nanoparticles, especially with respect to the human immune system. In the present study, the biological effects of dextran‑coated superparamagnetic iron oxide nanoparticles (Dex‑SPIONs) on human primary monocyte cells were evaluated. The results of the present study demonstrated that Dex‑SPIONs can be identified in phagosomes or freed in the cytoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The use of dextran with iron-oxide nanoparticles to improve biocompatibility was also studied using primary cells. Wu et al (2018) demonstrated that dextran-NPs had no significant effects on cell viability and apoptosis on human primary monocytes cells.…”
Section: Biocompatibility and Immune Escapementioning
confidence: 98%
“…The use of dextran with iron-oxide nanoparticles to improve biocompatibility was also studied using primary cells. Wu et al (2018) demonstrated that dextran-NPs had no significant effects on cell viability and apoptosis on human primary monocytes cells.…”
Section: Biocompatibility and Immune Escapementioning
confidence: 98%
“…A SPION-induced activation of monocytes as well as a phenotypic shift of M2-like towards M1-like macrophages have been repeatedly proposed ( Laskar et al, 2013 ; Rojas et al, 2016 ). Another publication proved an activation of MAPK signaling pathways in primary human monocytes that resulted in secretion of pro-inflammatory cytokines ( Wu et al, 2018 ). Sindrilaru and colleagues even suggested an iron-mediated regulation of the functional plasticity of monocytes ( Sindrilaru et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general, monocytes or macrophages are able to uptake SPIONs relatively rapidly (few hours) [114,170]. Wu et al demonstrated in primary human monocyte cells that SPI-ONs can be identified in phagosomes or in cytoplasm [171]. However, there are two noteworthy items regarding the cellular uptake of SPIONs: their size and their charge.…”
Section: Impact Of Spions On Monocytes and Macrophagesmentioning
confidence: 99%
“…Another important parameter to consider is the impact of SPIONs on cell viability in order to take advantage of the beneficial effects provided by anti-cancer therapies while minimizing the harmful adverse effects potentially induced by SPION vectors, especially since SPIONs cytotoxicity remains unclear [171]. In fact, several variables considerably complicate the evaluation of SPION cytotoxicity.…”
Section: Impact Of Spions On Monocytes and Macrophagesmentioning
confidence: 99%